2017
DOI: 10.1039/c7ra04173j
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical films of graphene nanoribbons and nanoflakes with natural polymers

Abstract: Graphene and its derivatives are promising as reinforcement for polymer nanocomposites. Additionally to their inherent outstanding mechanical properties, these nanoparticles may be functionalized to enhance their compatibility with the polymeric matrix and provide specific chemical and physical properties. In this work, new freestanding films (FS) based on chitosan (CHI), alginate (ALG) and functionalized graphene were developed using the layer-by-layer assembly. Suspensions of functionalized graphene nanoflak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
3
11
0
Order By: Relevance
“…Moreover, GO could be functionalized to further improve its electrical conductivity. 94,95 For example, Jin et al 94 introduced GO into the polyvinyl chloride/poly(lactic-co-glycolic acid) (PVC/PLGA) scaffold by electrospinning, and then GO-PVC/PLGA 96 composite scaffolds were immersed in hydrogen iodide solution to obtain rGO-PVC/PLGA scaffolds. The results showed that compared with GO-PVC/PLGA scaffolds, rGO-PVC/PLGA scaffolds had higher capacitance and better conductivity at a suitable voltage, which was due to the larger SSA of rGO-PVC/PLGA and the formation of more conjugated π-bonds on the surface of rGO.…”
Section: Excellent Electrical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, GO could be functionalized to further improve its electrical conductivity. 94,95 For example, Jin et al 94 introduced GO into the polyvinyl chloride/poly(lactic-co-glycolic acid) (PVC/PLGA) scaffold by electrospinning, and then GO-PVC/PLGA 96 composite scaffolds were immersed in hydrogen iodide solution to obtain rGO-PVC/PLGA scaffolds. The results showed that compared with GO-PVC/PLGA scaffolds, rGO-PVC/PLGA scaffolds had higher capacitance and better conductivity at a suitable voltage, which was due to the larger SSA of rGO-PVC/PLGA and the formation of more conjugated π-bonds on the surface of rGO.…”
Section: Excellent Electrical Propertiesmentioning
confidence: 99%
“…The results showed that compared with GO-PVC/PLGA scaffolds, rGO-PVC/PLGA scaffolds had higher capacitance and better conductivity at a suitable voltage, which was due to the larger SSA of rGO-PVC/PLGA and the formation of more conjugated π-bonds on the surface of rGO. In another case, Silva et al 95 introduced cyclic amine into graphene by 1.3-dipolar cycloaddition reaction, and then functionalized graphene was compounded with chitosan (CHI) and sodium alginate (ALG) to fabricate biofilms. The results showed that the introduction of functionalized graphene significantly reduced the resistivity of the thin films from 3.00 × 10 12 Ω m to 2.25 × 10 9 Ω m.…”
Section: Excellent Electrical Propertiesmentioning
confidence: 99%
“…Some useful features of such materials include biodegradability, low toxicity, and gel-forming ability, as well as reasonably low preparation costs. For instance, Silva et al [ 155 ] covalently functionalized graphene with N -benzyloxycarbonylglycine (Z-Gly-OH), in order to produce films through layer-by-layer deposition of chitosan and alginate chitosan. They found that the obtained films, beyond being cytocompatible, exhibited enhanced mechanical and electrical performance in comparison to the same systems without the functionalized graphene.…”
Section: Biomedical Engineeringmentioning
confidence: 99%
“…They found that the obtained films, beyond being cytocompatible, exhibited enhanced mechanical and electrical performance in comparison to the same systems without the functionalized graphene. These results suggest good potential for biomedical applications such as wound healing and regenerative medicine [ 155 ].…”
Section: Biomedical Engineeringmentioning
confidence: 99%
“…Composites of CNSs and biocompatible polymers can combine the properties of the two constituents and act as functional materials for a number of technological applications, [7,8] which include medical devices and implants [9][10][11][12], tissue engineering [13][14][15][16][17][18][19][20][21][22][23][24], drug delivery [25,26], bio-, green and wearable electronics [27][28][29], biosensing [29][30][31][32][33][34], soft robotics [35,36] and smart packaging [37][38][39].…”
Section: Accepted Manuscriptmentioning
confidence: 99%